The complete connectome of a learning and memory centre in an insect brain. - Eichler, K.; Li, F.; Litwin-Kumar, A.; Park, Y.; Andrade, I.; Schneider-Mizell, C.M.; Saumweber, T.; Huser, A.; Eschbach, C.; Gerber, B.; Fetter, R.D.; Truman, J.W.; et al. (Nature, 2017)
Associating stimuli with positive or negative reinforcement is essential for survival, but a complete wiring diagram of a higher-order circuit supporting associative memory has not been previously available. Here we reconstruct one such circuit at synaptic resolution, the Drosophila larval mushroom body. We find that most Kenyon cells integrate random combinations of inputs but that a subset receives stereotyped inputs from single projection neurons. This organization maximizes performance of a model output neuron on a stimulus discrimination task. We also report a novel canonical circuit in each mushroom body compartment with previously unidentified connections: reciprocal Kenyon cell to modulatory neuron connections, modulatory neuron to output neuron connections, and a surprisingly high number of recurrent connections between Kenyon cells. Stereotyped connections found between output neurons could enhance the selection of learned behaviours. The complete circuit map of the mushroom body should guide future functional studies of this learning and memory centre.